Stan liczebny Zjednoczonego Stronnictwa Ludowego w powiecie żarskim w latach 1949-1957 = The number of the United People's Party members in Żary county during the years 1949-1957 - Hładkiewicz, Wiesław; Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The incapacitation of the Polish people's movement by the communist party meant that the United People's Party (abbreviated ZSL, from the Polish term "Zjednoczone StronnictwoLudowe"), which was established in 1949, had to implement its program. It stood in contradiction to the peasants' expectations, because the collectivization, promoted by the People 's Party members, deprived them of their economic independence, which they held in high esteem.
Keywords: Zjednoczone Stronnictwo Ludowe (ZSL); Żary (woj. lubuskie); Polska - historia; po 1944 r.